The importance of nurses actions in basic health units and their impact on reducing maternal mortality (Research, Society and Development, 2022)
Objective: Identify in the literature the actions of nurses in pregnancy and postpartum care with repercussions on maternal mortality rates. Method: This is an integrative literature review with a qualitative and descriptive, documentary approach of dialectical epistemology. Results: Three categories were constructed in the literature: prenatal care and treatment, maternal mortality profile and nurse in prenatal care. Conclusion: Maternal mortality is still a public health problem, especially in Brazil. Reports of failures in the care of health professionals and social vulnerabilities contribute to the high number of maternal deaths still prevalent in Brazil.